Morphological Responses of a Light-Demanding Alstonia scholaris and a Shade-Tolerant Eusideroxylon zwageri to the Air Humidity and Light Intensity - Bambang Irawan; Rike Puspitasari Tamin; Rizky Ayu Hardiyanti (Jurnal Manajemen Hutan Tropika, 2021)
The response of tropical trees to the change of light intensity has been reported to be varied among different species. Some reports argued that the growth was increasing parallel to the increasing of light intensity, but other reports mentioned that the sensitivity to the light intensity was depending on the species. Another environmental factor that has been scientifically proven to affect tree growth is humidity. While humidity itself also directly affected by the light intensity in the forest ecosystems. Therefore, it is possible that the growth pattern of trees under different light intensities is also affected by air humidity under the canopy. This research aimed to study the growth response of a light-demanding Alstonia scholaris and a shade-tolerant Eusideroxylon zwageri to the different levels of air humidity and light intensity. The experiment was conducted in Jambi, Indonesia from April to November 2019. The experiment was carried out using split plot design with factorial treatments. The main plot was the air humidity with three levels and the sub plots was light intensity with five levels. Four replicates were applied. In general, the A. scholaris tends to be more sensitive to the humidity and light intensity compared to E. zwageri. In particular, A. scholaris tends to be more sensitive to the light intensity while, E, zwageri is more sensitive to the humidity. However, there is also strong indication that the effects of light intensity to the growth, especially for A. scholaris, was affected by the humidity level.